Qualitative Study of Implementation of KIA Program Achievements at South Balantak Community Health Center, Banggai Regency, Central Sulawesi Province - Bersa Efebtu; Ida Nuryati (Journal for Research in Public Health, 2022)
Background : Problems that are often faced include pregnant women giving more importance to birth attendants to check their pregnancy than health workers, which has an impact on the lack of achievement of maternal and child health programs. The aim of this research is to explore the implementation of the achievements of the KIA program at the South Balantak Health Center, Banggai Regency, Central Sulawesi Province. Method : The design of this research is qualitative descriptive. Informants are taken using techniques purposive sampling There were 4 Midwives who met the inclusion and exclusion criteria. Data collection techniques through in-depth interviews and documentation with informants. Qualitative data analysis techniques use data reduction, data presentation, drawing conclusions/Verification. Results : The research results show that the implementation of K1 and K4 program achievements of 88.68% is still below the target of 100%. The obstacles faced include the fact that there are still many pregnant women who do not report their pregnancies to the midwife. Implementation of delivery achievements by health workers was 67.33%, still below the target of 100%. Obstacles faced include the lack of public trust in health workers in assisting with childbirth, so pregnant women prefer traditional birth attendants to give birth. Government support such as holding cross-sector meetings to make a mutually signed decision that traditional birth attendants must not assist with childbirth themselves but must coordinate with health workers. Conclusion : Based on the research results, it was concluded that the implementation of K1 and K4 program achievements and childbirth by health workers was still below the national target of 100%. Thus, efforts can be made to meet targets that have not been achieved. Midwives must detect health problems in the village by carrying out integrated ANC examinations, ensuring that every pregnant woman has a MCH book, making home visits, ensuring that births are attended by health workers, making visits during postpartum period and neonatal visits.